Corellation of p53 expressions and histopathological grading in oral cavity squamous cell carcinoma - Silvi Kintawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Squamous cell carcinoma is a malignancy of oral cavity mostly occurred and can also metastasize. p53 gene is a tumor suppressor gene that plays an important role in carcinogenesis. The role of wild-type p53 is very important in suppressing the formation of a malignancy. p53 also has many other important functions. p53 is a suppressor of tumor/ cancer progression through the response of cell cycle to DNA damage and by giving time to repair DNA prior to replication of genes. p53 mutation, mostly occurs in a malignancy, so earlier histopathological transformation can be detected by observing p53 mutation. The prognosis of squamous cell carcinoma in oral cavity, therefore, depends on histopathological grading and clinical staging of the tumor. To enforce the histopathological grading, in addition based on histopathology differentiation, the earlier histopathological transformation can also be assessed. Purpose: This study aimed to determine the correlation of p53 expressions and histopathological grading in oral cavity squamous cell carcinoma. Method: This study was a retrospective study on 20 cases of oral cavity squamous cell carcinoma examined at Department of Pathology Anatomy in Hasan Sadikin Hospital in Bandung. Immunohistochemical examination was then performed using p53 antibodies to determine the correlation of p53 expression and histopathological grading in oral cavity squamous cell carcinoma to predict prognosis. Result: The overall results showed that there was no correlation between p53 expression and histopathological grading in oral cavity squamous cell carcinoma of the oral cavity although there was a very strong correlation between p53 expression and histopathological grading I (p<0.01). Conclusion: It can be concluded that there was no correlation between p53 expression and histopathological grading in oral cavity squamous cell carcinoma. Thus, p53 expression cannot be used to predict a prognosis.